Inner and outer potentialities: a spiritual approach to the problem of regenerative architecture and design - Wheeler, Andrea (Body and religion, 2023)
Ecological and regenerative architecture emphasizes the need for profound social and environmental change. Reconnection is a theme. Bill Reed (2007) has equated this sense of reconnectedness to a spiritual foundation in ecology, invoking the Latin term religio, which means "to bind" or "to connect." Chrisna du Plessis (2012) has traced regenerative design’s roots to ancient wisdom, citing teachings from the Upanishads. Regenerative architecture sets itself apart from many other sustainable design approaches that pin hopes on future technology. Regenerative design advocates for a profound shift in how we think, feel, and live in rejection of a technocratic paradigm. Its biophilic aesthetics celebrate a love of life. However, transitioning from one perspective on the environmental problem to a truly ecological future remains a complex challenge. In this context, the philosophical contributions of Luce Irigaray offer some ways forward. This article explores how Irigaray's understanding of a spiritual and relational practice of ecological reconnection can act as a bridge to new ways of thinking and feeling in relation. By emphasizing the development of a subtle sensory relationship between two subjects - two who are both equal and different - she opens up a path of deep ecological connection. Irigaray's ideas, while transcending conventional religious thinking, cite Christian, Hindu, and Buddhist traditions. In this expanded sense of regenerative design, we are not just the architects of the outer world, but also the architects of our own senses and aspirations, our own relationalities, our own sexual relationships, our own shared human experience.